ANTI-INFLAMMATORY EFFECTS OF ROOT BARK METHANOLIC EXTRACT OF BOSWELLIA DALZIELII IN ALBINO MICE - Vedekoi, Jeweldai; Dadaya, Elizé; Juliette, Koubé; Edima Carole Hélène; Sélestin, Sokeng Dongmo (Universal Journal of Pharmaceutical Research, 2024)
Background and objective: Boswellia dalzielii has been traditionally used in the Far North region (Cameroon) to treat fever, rheumatism, asthma and various inﬂammatory conditions. This investigation was designed to determine the anti-edematous and antioxidant properties to confirm its storied claims. Methods: The DPPH radical scavenging and reduced Fe3+to the Fe2+ assays were two methods used to evaluate the antioxidant activities. The swelling caused by carrageenan paw and xylene ear edema to cause inflammation were applied to evaluate the anti-inflammatory activities of the extract. The mechanisms of action of the methanol extract were evaluated in the serotonin test. Fever induced by yeast was exploited to value antipyretic activity in albinos animals. Diclofenac, ascorbic acid, and paracetamol were utilized as standard medicaments. Results: Results published the existence of cardiac glycosides, flavonoid, simple phenols, flavonoids, tannins, coumarins and alkaloids. The results indicated also no acute toxicity and the LD50 was above 3000 mg/kg. The methanolic extract exhibited the best activity IC50 (178.12 µg/mL) against DPPH radical with, which was comparable with ascorbic acid (179.12 µg/mL) and a strong reducing power with an IC50 of about 147.85 µg /mL. In addition, the roots extract of B. dalzielii significantly inhibited (p<0.001) the volume of paw edema, ear edema and the fever. Conclusion: Finally, the present study published clearly that the B. dalzielii methanolic extract (BDME) possess important antioxidant and anti-edematous effects. The phytoconstituents found in this methanol extract were responsible for the anti-inflammatory and antioxidant effects. Peer Review History: Received 21 May 2024; Reviewed 15 July 2024; Accepted 25 August; Available online 15 September 2024 Academic Editor: Dr. Gehan Fawzy Abdel Raoof Kandeel , Pharmacognosy Department, National Research Centre, Dokki, 12622, Giza, Egypt, gehankandeel9@yahoo.com Reviewers: Dr. Ogbonna B. Onyebuchi, Nnamdi Azikiwe University, Awka, Nigeria, summitpharm@yahoo.com Dr. George Zhu, Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com